2019
DOI: 10.1111/flan.12429
|View full text |Cite
|
Sign up to set email alerts
|

Impact of self‐reflection and awareness‐raising on novice French learners’ pronunciation

Abstract: Developing intelligible pronunciation is an important goal for language learners. Although it can be fostered through explicit instruction in communicative‐based courses, instructors need practical solutions to address their learners’ pronunciation individually. This one‐semester quasi‐experimental mixed methods study of 60 Generation Z novice French learners examined whether and how self‐reflection could be an effective learning strategy and an efficient complement in supporting the development of intelligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Furthermore, research has shown that pronunciation instruction leads to improved intelligibility by drawing learners' attention to specific pronunciation challenges that may impede their intelligibility (Derwing 2018;Levis 2018;Meritan and Mroz 2019).…”
Section: Foreign Language Pronunciation Instructionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, research has shown that pronunciation instruction leads to improved intelligibility by drawing learners' attention to specific pronunciation challenges that may impede their intelligibility (Derwing 2018;Levis 2018;Meritan and Mroz 2019).…”
Section: Foreign Language Pronunciation Instructionmentioning
confidence: 99%
“…This study thus focused on the explicit instruction of segmental and suprasegmental features hypothesized to impact intelligibility in French: the /y/-/u/ contrastive pair and liaisons, in a classroom setting. It is proposed here that using metacognitive strategies such as self-reflection may help draw learners' attention beyond specific phonological characteristics and raise phonological awareness (Meritan and Mroz 2019;Inceoglu 2021).…”
Section: Foreign Language Pronunciation Instructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another aspect, which is highly relevant nowadays, is the search for methodologies that would aim at raising efficiency of studying for will-be ESL teachers. One of them could be promoting self-reflection while studying a second language (Meritan & Mroz, 2019). This will allow university graduates to become independent, responsible individuals capable of critical thinking and at the same time reflective practitioners and skillful professionals (Asyari, Muhdhar & Susilo, 2016).…”
Section: Introductionmentioning
confidence: 99%